(untitled) (Revista Espinhaço, 2019)
The Jequitinhonha river watershed has been affected by land cover and use changes, resulting in local water resources quality impairment, since the beginning of the exploitation cycle of gold and diamond, especially during 18th century. Despite low water availability and pressures on local waters, water resources management tools such as water usage charge and qualitative granting of permits have not yet been fully implemented in the watershed. In this context, this paper aims to relate the evolution of land use and occupation in the basin with the water quality parameters that make up the Water Quality Index (WQI), identifying the main sources of pressure on water resources. Land cover and use were classified using data provided by MapBiomas Project in 2000 and 2014, while water quality data were obtained from the monitoring program conducted by the Minas Gerais Institute for Water Management (IGAM). Data analysis was conducted through descriptive statistical analysis and construction of multiple regression models. The results showed that agriculture and livestock activities were the ones that most influenced the water quality in the watershed during the study period (2000 and 2014), especially on Nitrate, Total Solids and pH values. In addition, the results in the dry season were more significant compared to the rainy season, probably due to greater environmental stability in the drought. Thus, the deterioration of environmental quality in the watershed, mainly due to the increase of areas with anthropogenic activities to the detriment of natural areas, has impaired its water quality.